(untitled) (VITAE Academia Biomédica Digital, 2025)
At the end of 2019, a new disease, similar to severe acute respiratory syndrome (SARS) associated with SARS‑CoV was reported in Wuhan, China. It was quickly discovered that the etiological factor of the new disease (COVID‑19) was a previously unknown SARS coronavirus 2 (SARS‑CoV‑2). The global spread of of COVID‑19 has lead to the declaration of a pandemic status in 2019‑2020 as declared by the World Health Organization and Public Health Emergency of International Concern. SARS‑CoV‑2 characterizes with high epidemic potential and is effectively disseminated between humans. SARS‑CoV and SARS‑CoV‑2 are closely related pathogens. Their prime route of distribution is air‑droplet transmission. Combating infectious diseases disseminated by inhalation is very difficult, and mainly relies on the use of vaccines. However, despite the lack of an effective anti‑SARS‑CoV vaccine and specific antiviral drugs, the strict sanitary procedures proved to be sufficient to stop the SARS epidemic in June 2003. However, epidemic research has indicated that SARS‑CoV‑2 is transmitted in humans significantly more effectively than SARS‑CoV; therefore, the COVID‑19 pandemic continues to expand. This indicates that the so far anti‑epidemic activities to control COVID‑19 are insufficient. In the current review, the possibility of using interferon α (IFN‑α) as a preventive agent of COVID‑19 is discussed. The current data concerning anti‑COVID‑19 vaccines and specific drugs against SARS‑CoV‑2 are also discussed. The aim of the current review is to contribute to the introduction of a more efficient strategy in the protection of the human population against COVID‑19.